Microencapsulation of flaxseed oil in flaxseed protein and flaxseed gum complex coacervates. (August 2016) - Kaushik, Pratibha; Dowling, Kim; McKnight, Stafford; Barrow, Colin.J.; Adhikari, Benu
Abstract: Flaxseed oil, a rich source of omega-3 fatty acids, was microencapsulated in a novel matrix formed by complex coacervation between flaxseed protein isolate (FPI) and flaxseed gum (FG). This matrix was crosslinking with glutaraldehyde. Liquid microcapsules with three core (oil)-to-wall ratios (1:2, 1:3 and 1:4) were prepared and spray-dried or freeze-dried to produce powders. The microencapsulation efficiency, surface oil, morphology and oxidative stability of these microcapsules were determined. The spray-dried solid microcapsules had higher oil microencapsulation efficiency, lower surface oil content, smoother surface morphology and higher oxidation stability than the freeze-dried microcapsules. The highest microencapsulation efficiency obtained in spray-dried microcapsules was 87% with a surface oil of 2.78% at core-to-wall ratio 1:4 and oil load 20%. The oxidation stability obtained from spray-dried microcapsules at core-to-wall ratio of 1:4 was nearly double that of the unencapsulated flaxseed oil. Graphical abstract: Highlights: Flaxseed protein and flaxseed gum coacervates were used to encapsulate flaxseed oil. Crosslinking of coacervates appears to provide a more defined outer wall for encapsulated oil. Spray drying yielded higher microencapsulation efficiency than freeze drying. Oxidative stability of flaxseed oil got doubled by microencapsulation and spray drying.